👤
a fost răspuns

Să se rezolve ecuația (3x-1)/(x+1)+(x+1)/(2x-1)=3
P.S.
Solutia este x apartine(1,5), dar nu stiu cum a dat rezultatul acesta.


Răspuns :

Alitta
[tex]\Rightarrow\;\frac{3x-1}{x+1}+\frac{x+1}{2x-1}=3\\
\frac{(3x-1)(2x-1)+(x+1)(x+1}{(x+1)(2x-1}=3\;\;|\;\cdot(x+1)(2x-1)\\
(3x-1)(2x-1)+(x+1)^2=3(2x-1)(x+1)\\
6x^2-2x-3x+1+x^2+2x+1=6x^2+6x-3x-3\\
restrangem\;termenii\;asemenea\;\\
\Rightarrow\;\;x^2\,-\;6x+5=0\\
adica:\;x^2-x-5x+5=x(x-1)-5(x-1)=0\\
de\;unde\;\;\\
x-1=0\;\;\rightarrow\;\;x_{1}=1\;si\\
x-5=0\;\;\rightarrow\;\;x_{2}=5\\
deci:\;S(x_{1};x_{2})=(1\,;\,5)
[/tex]